Vertebrate endocrinology - Norris, David O.; Carr, James A (Waltham : Academic Press, 2013)
Vertebrate Endocrinology represents more than just a treatment of the endocrine system-it integrates hormones with other chemical bioregulatory agents not classically included with the endocrine system. It provides a complete overview of the endocrine system of vertebrates by first emphasizing the mammalian system as the basis of most terminology and understanding of endocrine mechanisms and then applies that to non-mammals. The serious reader will gain both an understanding of the intricate relationships among all of the body systems and their regulation by hormones and other bioregulators, but also a sense of their development through evolutionary time as well as the roles of hormones at different stages of an animal's life cycle.
Appendix A-H 529-570p.; Index 571-585p.
Keywords: Vertebrate reproduction; Non-mammalian; Hypothalamus